• Предмет: Алгебра
  • Автор: zarinarustamovna06
  • Вопрос задан 4 года назад

упростите выражение ​

Приложения:

zarinarustamovna06: помогите пожалуйста прошу вас

Ответы

Ответ дал: FaerVator
4

\LARGE{\mathbf{ \frac{ \cos {}^{2}( \frac{3\pi}{2}    +  \alpha )}{1 -  \cos \alpha } }}  +  \sin( \frac{3\pi}{2}  +  \alpha )  +  \tan( \frac{\pi}{2} +  \alpha  ) \cdot \cot( \frac{3\pi}{2} +  \alpha    )   = \frac{ \sin {}^{2} \alpha  }{1 -  \cos \alpha }   + ( -  \cos \alpha ) + ( -  \cot \alpha ) \cdot( -  \tan \alpha ) =  \frac{ \sin {}^{2} \alpha  }{1 -  \cos \alpha }    - \cos \alpha +   \cot \alpha \cdot  \tan \alpha  = \frac{1- \cos {}^{2} \alpha  }{1 -  \cos \alpha }    - \cos \alpha +    \frac{1}{ \tan \alpha  } \cdot  \tan \alpha =  \frac{(1 -  \cos \alpha )(1 +  \cos \alpha )  }{1 -  \cos \alpha  }  -  \cos \alpha  +  \frac{1}{ \tan \alpha  } \cdot \tan \alpha  = 1 +  \cos \alpha  -  \cos \alpha  + 1 =1 + 1 =  \boxed2


zarinarustamovna06: благодарю
Похожие вопросы